Identification of Nocardia and non‐tuberculous Mycobacterium species by MALDI‐TOF MS using the VITEK MS coupled to IVD and RUO databases - David Rodríguez‐Temporal; Margarita Estreya Zvezdánova; Pablo Benedí; Mercedes Marín; Mario Blázquez‐Sánchez; María Jesús Ruiz‐Serrano; Patricia Muñoz; Belén Rodríguez‐Sánchez (Microbial Biotechnology, 2023)
Abstract Identification of Nocardia and Mycobacterium species by matrix‐assisted laser desorption/ionization‐time of flight mass spectrometry (MALDI‐TOF MS) is still a challenging task that requires both suitable protein extraction procedures and extensive databases. This study aimed to evaluate the VITEK MS Plus system coupled with updated RUO (v4.17) and IVD (v3.2) databases for the identification of Nocardia spp. and Mycobacterium spp. clinical isolates. Sample preparation was carried out using the VITEK MS Mycobacterium/Nocardia kit for protein extraction. From 90 Nocardia spp. isolates analysed, 86 (95.6%) were correctly identified at species or complex level using IVD and 78 (86.7%) using RUO. Only two strains were misidentified as other species pertaining to the same complex. Among the 106 non‐tuberculous Mycobacterium clinical isolates tested from a liquid culture medium, VITEK MS identified correctly at species or complex level 96 (90.6%) isolates in the IVD mode and 89 (84.0%) isolates in the RUO mode. No misidentifications were detected. Although the IVD mode was unable to differentiate members of the M. fortuitum complex, the RUO mode correctly discriminated M. peregrinum and M. septicum. The robustness and accuracy showed by this system allow its implementation for routine identification of these microorganisms in clinical laboratories.